NB AND PB IN OCEANIC BASALTS: NEW CONSTRAINTS ON MANTLE EVOLUTION - Hofmann A.W.; Jochum K.P.; Seufert M.; White W.M. (My University, 1986)
Nb/U ratios and Ce/Pb ratios are surprisingly uniform at 47 _+ 10 and 25 ___ 5, respectively, in both mid-ocean ridge basalts (MORB) and ocean island basalts (OIB). We show that these ratios also characterize the mantle sources of both types of oceanic basalts, and that these mantle sources have been fractionated from the primitive-mantle ratios of Nb/U = 30 and Ce/Pb = 9. The respective ratios in the continental crust are even lower, namely Nb/U = 10 and Ce/Pb = 4. Therefore, OIB cannot be derived from a primitive portion of the mantle, from mixtures of primitive and depleted mantle, or from recycled continental crust. The portion of the primitive mantle from which the continental crust and the residual (MORB plus OIB source) mantle has been differentiated is estimated to be about 50%, but the uncertainties are such that whole-mantle differentiation cannot be ruled out. We propose the following simple model to satisfy the above new constraint on mantle composition: The differenti- ated part of the mantle, chemically depleted after separation of the major portion of the continental crust, was subsequently internally rehomogenized. This depleted but chemically homogeneous mantle region was then differenti- ated into MORB and OIB source regions. The primary (continental crust-mantle) differentiation fractionated the Nb/U and Ce/Pb ratios, but the secondary (MORB source-OIB source) differentiation did not. Following the model of Hofmann and White [1,2], we suggest that the mechanism chiefly responsible for the secondary differentiation is the formation and subduction of oceanic crust. It is volumetrically by far the most important ongoing differentiation process on Earth and, over the course of Earth history, has created at least ten times as much oceanic crust as the present-day volume of continental crust. Because the residual mantle was homogenized (though depleted in incompatible elements) after the primary differentiation, the isotopic and chemical heterogeneities exemplified by the isotope ratios of Sr, Nd, Hf, and Pb, and by trace element ratios such as K/Rb, were created during the secondary differentiation. During this process, the bulk partition coefficients of Nb and Ce were very similar to those of U and Pb, respectively. This is in contrast with the primary differentiation, during which U was more incompatible than Nb, and Pb more incompatible than Ce.